FROM NEEDLE TO NUMBERS: NAVIGATING THE BLOOD EXTRACTION PROCESS, LAB MACHINES, AND COMPLETE BLOOD COUNT TECHNIQUES - Fahad mahdi Mohammed Al sulayyim, Muslih mahdi Mohammed Al sulayyim, Abdullah lqal Al yami, Hussain Mesfer Hamad Alsaleem, Abdullah Mohammed Salem Alsallum, Rashed Saeed Hadi Al Aba Taheen, Hassan Muidh Hamel Lasslom, Ibrahim Saleh Hamad Alsallum (Chelonian Research Foundation, 2023)
Extraction and examination of blood components are fundamental for present-day diagnostics. This article shows blood inspecting strategies, research facility tests, and strategies for complete blood count (CBC). By combining existing information, strategy, and strategy, this investigation points to the complex preparation of blood screening, from the beginning extraction to the last translation of comes about. Critical regions of the center incorporate different extraction strategies such as venipuncture and finger pricking, the part of robotized hematology frameworks in research facility testing, and strategies utilized for CBC testing, counting impedance strategies, and stream cytometry. Through this inquiry, this article points to understanding the complexity of blood investigation, making a difference in how specialists progress the symptomatic preparation and progress perception results.